Water conservation decision-making by producers on the Ogallala Aquifer - Carnes, Rebekah (Kansas State University, 2020)
This study investigates the roles of values, beliefs, and norms in water conservation decisions made by producers on the Ogallala Aquifer, in order to better understand the motivating factors that could lead toward environmental sustainability in this region of groundwater depletion. I focus on an over-arching question: how do farmers make decisions regarding water conservation? This question is broken into two specific sub-questions. First, how does culture affect decision-making? How do farmers’ beliefs, values, political ideologies, and education influence their concern for the environment, measured by the extent to which they elevate guiding principles such as “respecting the earth, harmony with other species, protecting the environment, preserving nature, unity with nature, and fitting in with nature”? Secondly, how does the climate, and potentially climate change, affect the attitudes that prompt and justify decisions? This research relies on data from the 2019 Ogallala Producer Survey, and Climate data from the USGS in corresponding counties, and examines these questions through a series of regression models.
Keywords: Water conservation; Decision-making; Ogallala aquifer; Irrigation norms; Environmental values; Environmental beliefs